2020
DOI: 10.1126/sciadv.aaz9072
|View full text |Cite
|
Sign up to set email alerts
|

Integrator restrains paraspeckles assembly by promoting isoform switching of the lncRNA NEAT1

Abstract: RNA 3′ end processing provides a source of transcriptome diversification which affects various (patho)-physiological processes. A prime example is the transcript isoform switch that leads to the read-through expression of the long non-coding RNA NEAT1_2, at the expense of the shorter polyadenylated transcript NEAT1_1. NEAT1_2 is required for assembly of paraspeckles (PS), nuclear bodies that protect cancer cells from oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…We previously showed that Integrator is involved in the 3′ end processing of multiple classes of noncoding RNAs, including snRNAs, eRNAs, and NEAT1 ( 22 , 23 , 45 ). Moreover, we recently showed that Integrator terminates transcripts associated with paused RNAPII and facilitates transcriptional elongation through the subsequent recruitment of an elongation-competent RNAPII complex ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that Integrator is involved in the 3′ end processing of multiple classes of noncoding RNAs, including snRNAs, eRNAs, and NEAT1 ( 22 , 23 , 45 ). Moreover, we recently showed that Integrator terminates transcripts associated with paused RNAPII and facilitates transcriptional elongation through the subsequent recruitment of an elongation-competent RNAPII complex ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…[34,37] At the post-transcriptional level, NEAT1 is mainly regulated by altered 3'-end processing to adjust the NEAT1_1:NEAT1_2 ratio. [21,38] Several regions of NEAT1 are important, including near the polyA site of NEAT1_1 where proteins including HNRNPK and TDP43 bind and alter the processing of NEAT1_1 (Figure 2C). [39] When paraspeckles increase a variety of different gene regulatory changes can come into play to aid the cell.…”
Section: Paraspeckles Are Membraneless Organelles Built On the Lncrnamentioning
confidence: 99%
“…Finally, the integrator complex has been shown to associate with active enhancers and increases enhancer-promoter communication 77 . Decreased expression of INTS11, the catalytic subunit of the complex, promotes read-through transcription at polyadenylation sites and shifts alternative isoform expression towards the distal isoform 29,78 . This suggests that increased association of integrator at active enhancers could prevent read-through and could increase CPA activity.…”
Section: Discussionmentioning
confidence: 99%